Kedudukan Perjanjian Pra-Nikah Sebagai Pemisah Atas Harta Pribadi Dengan Harta Bersama Dalam Usaha Perseroan Terbatas (PT) - Pinareswati, Shafira Tri; Mila Fitriana, Zuhda (Lex Stricta : Jurnal Ilmu Hukum, 2025)
In general, a Prenuptial Agreement is an agreement made before a marriage takes place. In carrying out a Prenuptial Agreement, both parties are not yet husband and wife. In accordance with agreements in general, a Prenuptial Agreement has legal force and regulations that must be obeyed by the parties during the marriage. Regarding the contents of the Prenuptial Agreement, it is adjusted to mutual agreement. As someone who works in the Limited Liability Company sector chooses to use a Prenuptial Agreement to separate personal assets from joint assets. The results of this study discuss the position of a prenuptial agreement to protect assets during marriage, as well as analyzing prenuptial agreements to minimize unwanted risks.